The effects of Cr on isothermal oxidation behavior of Fe-30Mn-6Si alloy - Balo, S. Nevin; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2013)
The oxidation behavior of Fe-Mn-Si and Fe-Mn-Si-Cr alloys was investigated under isothermal atmosphere. The oxidation rates of the alloys are significantly increased with isothermal temperature. The oxidation of FeMnSi alloy is decreased with incorporation of Cr into FeMnSi alloy. The oxidation activation energies of the Fe-Mn-Si and Fe-Mn-Si-Cr alloys were found to be 126.79 kJ/mol and 105.74 kJ/mol, respectively. The activation energy is decreased with incorporation of Cr. The obtained oxides were found to be SiO2, MnO and MnO2 for FeMnSi. With the incorporation of Cr, the CrO3, SiO2 and MnO oxides were observed. It is evaluated that the oxidation behavior of FeMnSi shape memory is decreased with incorporation of Cr into the same shape memory alloy. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Isothermal oxidation; Fe-Mn-Si and Fe-Mn-Si-Cr alloys